Parking Cross Prototype Using RFID as a Microcontroller Based Payment Tool - Julham Julham; Putri Ayu Sitorus (International Journal of Data Science, Computer Science and Informatics Technology (InJODACSIT), 2021)
The process control of the parking cross which is manually still has weaknesses. This weakness can be exemplified by the obligation to place someone to guard the bar so that it can be opened and closed when guests come in and out. And on the other hand the guards cannot memorize the faces of the guests who are allowed to enter through the bar. A well-structured parking system that is able to offer a variety of solutions to existing parking problems is the most needed parking system today. RFID (Radio Frequency Identification) can be the answer to build this system. In this research, a parking barrier lock system design automatically uses RFID. RFID is a technology to identify an object automatically (Automatic Identification System). The process of transferring data on RFID can occur without having to touch (contactless) between devices. RFID consists of 2 main components, namely a tag and a reader. The RFID Reader is used to read the ID numbers on the RFID card, and the Arduino Uno is the controller. With the development of a parking system using RFID, changing the manual parking system to a computerized system that provides a lot of facilities and controls that are more effective and efficient.